PENGARUH KOMPETISI BANK TERHADAP STABILITAS SISTEM KEUANGAN PERBANKAN (STUDI KASUS PADA KBMI IV TAHUN 2019-2022) - Febryianti, Elvira; Yenny Kornitasari (Contemporary Studies in Economic, Finance and Banking, 2024)
The emergence of banking as an intermediary institution plays a very important role in the economy because it is the heart that must pump "money" and distribute it to all organs that need the money. Therefore, it is very important to maintain the stability of the banking financial system. The development of the banking system can trigger competition in the banking industry which can affect banking stability. This research was conducted to determine the effect of bank competition on the stability of the banking financial system. This research focuses on KBMI 4 data which is a large bank HHI index, market share and Loan to Deposit Ratio (LDR) used as a proxy for competition and Non-Performing Loans (NPL) as a proxy for banking financial stability. The analysis technique used is Panel Data Regression with KBMI 4th ​​quarter data for 2019-2022. Of these three variables, the HHI index and Loan to Deposit Ratio (LDR) variables have a significant effect on Non-Performing Loans (NPL). Meanwhile, the market share variable has no significant effect on Non-Performing Loans (NPL).